Acoustic and thermodynamic study of D-Panthenol in aqueous solutions of glycol at different temperatures. (November 2018) - Chakraborty, Nabaparna; Kumar, Harsh; Kaur, Kirandeep; Juglan, K.C.
Highlights: The measurements of density and ultrasonic velocity of EG, DEG and TEG in aqueous D-Panthenol solution are reported in this study. Along with increase in the concentration of D-Panthenol and the increase in molar mass of glycols, the interaction extent increases. The pair wise interaction between glycols and D-Panthenol is suggested by the V AB and K AB values. From the results it is concluded that (ion-hydrophilic) and (hydrophilic-hydrophilic) interactions are present. Abstract: The interaction of EG, DEG and TEG with biologically active D-Panthenol, as the function of temperature has been investigated by the combination of acoustic and volumetric methods. Speeds of sound and densities of EG, DEG and TEG in (0.05, 0.10 and 0.15) mol·kg −1 in aqueous solutions of D-Panthenol have been measured at T = (293.15, 298.15, 303.15 and 308.15) K. From the density data, the apparent molar volume ( V ϕ 0 ) and standard partial molar volume of transfer Δ V ϕ 0 for EG, DEG and TEG in aqueous D-Panthenol solutions have been determined. From the speed of sound data, the partial molar isentropic compression K ϕ, s and the partial molar isentropic compression of transfer Δ K ϕ, s 0, have been determined. The pair and triplet interaction coefficient have also been estimated.